Synthesis of porous high-temperature superconductors via a melamine formaldehyde sacrificial template. Issue 14 (29th June 2022) - Luke, Emily J.; Potticary, Jason; Terry, Lui R.; Doan, Huan V.; Hinoplen, Roemer; Cross, Sam; Ting, Valeska P.; Friedemann, Sven; Hall, Simon R.
Abstract : The synthesis of porous high-temperature superconductors has been achieved for the first time using melamine formaldehyde as a sacrificial template. Abstract : Nanostructured high-temperature superconductors YBa2 Cu3 O6+ δ and Bi2 Sr2 CaCu2 O8+ δ were synthesised using a melamine formaldehyde sponge as a sacrificial template, via three solution-based approaches. In the case of YBa2 Cu3 O6+ δ, a modified Pechini method produced a material with a superconducting transition at 92 K and a specific surface area of 4.22 m 2 g −1 . Further analysis with Hg porosimetry determined that the sponge exhibited a porosity of 82%. In the case of Bi2 Sr2 CaCu2 O8+ δ, this method produced a material that exhibited superconductivity at 86 K with a specific surface area of 9.62 m 2 g −1 . Hg-porosimetry determined that the BSCCO sponge exhibited a porosity of 78%.